A study on clinical profile of patients with ulcerative colitis and association of neutrophil-lymphocyte ratio with disease severity - Dhotra, Arun; Shaikh, Kani; A., Anand; A. R., Akilandeshawari; N., Arun (International Journal of Research in Medical Sciences, 2022)
Background: Ulcerative colitis (UC) is an immune mediated chronic inflammatory condition. Systemic inflammatory conditions like UC are associated with increased WBC count and inflammatory markers. A growing body of evidence suggested that neutrophil-lymphocyte ratio (NLR) is a useful bio-maker of systemic inflammatory response. Methods: An observational study was carried out at department of digestive health and diseases, government Kilpauk medical college, Chennai, from October 2020 to September 2021. All the patients diagnosed as UC were included. Age and sex matched controls were included. Clinical details and colonoscopic findings and laboratory values including WBC, ESR, NLR were noted and analyzed. Results: A total of 70 patients of UC came during this period. The 32 patients had active UC and 38 patients had inactive UC. 40 age and sex matched controls were included. Mean age of the patients with UC was 40.76±9.81 years. Out of UC cases, 58.57% were females. Maximum patients presented with bloody diarrhoea (88.57%) and left sided colitis was more common (41.43%). On analyzing laboratory values, the NLR values of active UC group were significantly elevated compared with those of the patients with inactive UC and controls (2.84±0.66, 2.05±0.21 and 1.60±0.25 respectively) p<0.001. Conclusions: UC is an inflammatory condition with bloody diarrhoea as the primary presenting symptom. NLR was significantly elevated in patients with active disease. NLR is a useful biomarker of systemic inflammatory response and it maybe a promising marker of disease severity in UC.